2013
DOI: 10.35808/ersj/391
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Capital Structure in Emerging Capital Markets: Evidence from Serbia

Abstract: This paper explores the determinants of the capital structure of Serbian firms listed on the regulated market using panel data. We model the leverage ratio as a function of firm-specific characteristics. The findings indicate the emerging character of Serbian corporate environment. We document that Serbian firms tend to have much lower debt ratio and that they rely more heavily on short-term than long-term debt compared to firms coming from other transitional economies. The study shows that there is a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 67 publications
(68 reference statements)
5
26
0
3
Order By: Relevance
“…This is quite surprising as Titman and Wessels [1988], Rajan and Zingales [1995], Booth et al [2001], Baker and Martin [2011] found positive relation between tangibility and capital structure. Still, Bauer [2004] for Czech companies and Malinić et al [2013] for Serbian companies found a negative relation and concluded that a negative relation is present in empirical studies for developing countries (especially CEE), whereas developed countries exhibit a positive relation.…”
Section: Static Ratios Of Capital Structure and Its Determinantsmentioning
confidence: 99%
“…This is quite surprising as Titman and Wessels [1988], Rajan and Zingales [1995], Booth et al [2001], Baker and Martin [2011] found positive relation between tangibility and capital structure. Still, Bauer [2004] for Czech companies and Malinić et al [2013] for Serbian companies found a negative relation and concluded that a negative relation is present in empirical studies for developing countries (especially CEE), whereas developed countries exhibit a positive relation.…”
Section: Static Ratios Of Capital Structure and Its Determinantsmentioning
confidence: 99%
“…The study also indicated that there was a significant negative impact on liquidity, tangibility, profitability and cash gap on the debt ratios. The leverage level of Serbian firms was positively affected by income volatility and growth opportunities [Malinić, Denčić-Mihajlov, Ljubenović, 2013]. The study of Central and Eastern Europe firms tested the characteristics of the firms that affected the capital structure of micro, small, and medium-sized firms.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Business risk -(Trade-off theory) + (Pecking-order theory) Bauer, 2004;Dung, 2015;Frank, Goyal, 2009;Titman, Wessels, 1988 Profitability -(Pecking-order theory) + (Trade-off theory, Agency theory, Free Cash Flow theory) Ivashkovskaya, Solntseva, 2007;Jensen, 1986;Myers, Majluf, 1984;Rajan, Zingales, 1995;Sheluntcova, 2014 Firm size -(Pecking-order theory) + (Trade-off theory) Frank, Goyal, 2009;Ivashkovskaya, Solntseva, 2007;Nunkoo, Boateng, 2010;Sheluntcova, 2014;Titman, Wessels, 1988 Growth opportunities -(Trade-off theory, Agency theory, Free Cash Flow theory) + (Pecking-order theory) Dung, 2015;Malinić, Denčić-Mihajlov, Ljubenović, 2013;Myers, Majluf, 1984;Smith, Watts, 1992 Tangibility -/+ (Pecking-order theory) + (Trade-off theory, Agency theory)…”
Section: Determinants Effects Evidencementioning
confidence: 99%
See 2 more Smart Citations